Pemberdayaan dan Pemulihan Sosial Ekonomi Masyarakat Terdampak Bencana Hidrometeorologi melalui Penguatan UMKM dan Dukungan bagi Anak Disabilitas di Kabupaten Pidie Jaya - Mujiburrahman Mujiburrahman; Ibrahim Chalid; Aflia Riski; Nulwita Maliati; Maisyura Maisyura; Suadi Suadi; Awaludin Arifin; Cut Andyna; Beeri Burman; Fahmi Sya’ya; Bagong Suyanto; Ikhsan Rosyid Mujahidul Anwari (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2026)
This study presents a collaborative community service program designed to accelerate the socio-economic recovery of communities affected by hydrometeorological disasters in Pidie Jaya Regency, Indonesia. The program addressed the challenge of promoting sustainable recovery beyond emergency response by strengthening Micro, Small, and Medium Enterprises (MSMEs) and supporting vulnerable groups, particularly children with disabilities. A participatory approach was employed through collaboration among academics, local authorities, community organizations, and volunteers. The activities included emergency relief distribution, MSME management training, business capital assistance, mentoring, and inclusive educational support for children with disabilities. The findings demonstrate that emergency assistance effectively fulfilled immediate community needs, while MSME recovery showed varying levels of progress depending on the extent of disaster-related losses and business capacity. Continuous mentoring and institutional support proved essential for long-term business recovery. The program also enhanced community participation and social inclusion. Overall, integrating emergency relief with sustainable economic empowerment and inclusive social support provides an effective strategy for strengthening post-disaster resilience and community recovery.